Excess Body Weight and Cancer-Related Fatigue, Systemic Inflammation, and Serum Lipids in Breast Cancer Survivors. (18th August 2021) - Inglis, Julia E.; Kleckner, Amber S.; Lin, Po-Ju; Gilmore, Nikesha J.; Culakova, Eva; VanderWoude, Amy C.; Mustian, Karen M.; Fernandez, I. Diana; Dunne, Richard F.; Deutsch, Jeremy; Peppone, Luke J.
Abstract: Background: Cancer-related fatigue (CRF) is a common side effect impacting breast cancer survivors. Research points to a relationship between obesity and CRF in breast cancer survivors related to elevated systemic inflammation and metabolic alterations. Methods: This cross-sectional study examined the relationship of obesity to CRF, inflammatory markers and serum lipids through a secondary analysis of a nationwide randomized controlled trial. Breast cancer survivors with CRF were categorized based on BMI category. Symptoms of CRF, inflammatory markers and serum fatty acids were assessed among groups. Results: There were 105 breast cancer survivors in the analysis. BMI was positively associated with CRF based on MFSI General ( p  = 0.020; 95% C.I. 0.024, 0.273) and MFSI Physical ( p  = 0.013; 95% C.I. 0.035, 0.298) subscales. TNF-α ( p  = 0.007; 95% C.I. 0.007, 0.044), and IL-6 ( p  = 0.020; 95% C.I. 0.006, 0.073) were elevated in the obese. Monounsaturated fatty acid levels ( p  = 0.047; 95% C.I. 0.000, 0.053) and the omega-6 to omega-3 fatty acid ratio were associated with obesity ( p  = 0.047; 95% C.I. 0.002, 0.322). Conclusions: Obese breast cancer survivors had greater levels of CRF, inflammatory markers and certain fatty acids. Inflammatory markers and fatty acids were not found to have any mediating or positive association with CRF variables in this analysis. NCT02352779.